Job Satisfaction and Marital Satisfaction Work Family Conflict In Mothers Who Work As Teachers - Agus Suswanto; Edwina Noor Triana Dewayani Soeharto (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The advancement of information technology which is growing rapidly in the era of the wave of the industrial revolution has become one of the drivers in changing society. One of the forces of change and development in society is marked by the unstoppable ientry iwomen intoi ithe iworld iof iwork. Some iof ithe impetus that makes many women become workers include economic factors, the fulfillment of a decent standard of living and the increasing demand for female workers. Women who work have role demands simultaneously coming from various types of work responsibilities and roles as wives that can cause conflict both in work and family one of them is a female teacher. Thei iresearch imethod is iquantitative iwith 153 isample female teachers with certain criteria, thei idata werei ianalyzed iusing multiplei ilinear iregression. The results showed that there was a simultaneous irelationship ibetween ijob isatisfaction iand marital satisfaction iwith iWork-Family iConflict on female teachers iwith iF valuei iof 120,472 (p<0.01). The effective contribution iof ijob isatisfaction and marital satisfaction to predict iWork-Family Conflict is 61.6% while ithe iremaining 38.4% isi iinfluenced iby iother ifactors inot examined ini ithis istudy. Kemajuan teknologi informasi yang berkembang pesat di era gelombang revolusi industri menjadi salah satu pendorong dalam perubahan masyarakat. Suatu kekuatan perubahan dan perkembangan di dalam masyarakat salah satunya ditandai dengan masuknya perempuan dalam dunia kerja yang tidak terbendung lagi. Beberapai dorongani yangi membuati ibanyaknya iwanita iyang imenjadi pekerjai idiantaranya iadalah ifaktor iekonomi, ipemenuhan istandar ihidup iyang layaki iserta ipeningkatan ipermintaan itenaga ikerja iwanita. Perempuan yang bekerja memiliki tuntutan peran secara bersamaan datang dari berbagai jenis tanggung jawab pekerjaan dan peran sebagai isteri yang dapat menimbulkan konflik baik dalam pekerjaan maupun keluarga salah satunya adalah guru perempuan. Metode penelitian adalah kuantitatif dengan sampel yaitu 153 guru perempuan dengan kriteria terentu, data dianalisa menggunakan iregresi ilinier berganda. iHasil ipenelitian imenunjukkan bahawa iterdapat hubungan isecara bersamaan kepuasan kerja dan kepuasan perkawinan dengan Work-Family Conflict pada guru wanita dengani nilaii iF isebesar 120,472 (p<0,01). Sumbangan efektif dari kepuasan kerja dan kepuasan perkawinan untuk memprediksi iWork-Family Conflicti iadalah isebesar 61,6% sedangkan isisanya 38,4% idipengaruhi ioleh ifaktor laini iyang itidak iditeliti idalam ipenelitian iini.